The effect of fermentation water spinach (ipomoea aquatica forsk.) Flour on performance super native chicken grower phase - Silitonga, Lisnawaty; Yuanita, Iis; Pudjirahayu, Asri; ma'rifah, siti; Siburian, Rusmayanti (Jurnal Nutrisi Ternak Tropis dan Ilmu Pakan, 2024)
The aim of the study was to determine the effect of water spinach fermentation (Ipomoea aquatica Forsk.) on the performance and Income Over Feed Cost (IOFC) of super native chickens in at grower phase. The material used water spinach flour which was fermented anaerobically for 14 days then mixed in the diets. The research treatment used super free-range chicken aged 4-8 weeks, EM4, and granulated sugar. The rations consisted of ground corn, fine bran, palm kernel cake, tofu dregs, fish meal, minerals and fermented water spinach flour. The study used a completely randomized design (CRD) with 4 treatments and 6 replications, each replication containing 4 free-range chickens in the grower phase of 4 weeks old. P0 (basal diet without fermented water spinach flour). P1 (basal diet with 3% fermented water spinach flour), P2 (basal diet with 6% fermented water spinach flour), P3 (basal diet with 9% fermented water spinach flour). Parameters observed included ration consumption (g), body weight gain (g), ration conversion, final body weight (g), Income Over Feed Cost (IOFC), and mortality. The results of the analysis showed that the provision of fermented water spinach flour was not significantly different from ration consumption, body weight gain, feed conversion ration, and final body weight. The use of fermented water spinach flour up to 9% in the growt of super native chickens being quite good due to the increasing by feed intake, body weight gain, final final weight, and low feed conversi ration. The best level of using fermented water spinach flour on the Income Over Feed Cost (IOFC) of super native chickens in the grower phase is in the P2 treatment, which 6% could be provides greater benefits than other treatments. Percentage mortality was low. Key words : Super chicken grower phase, fermented water, spinach flour